2009
DOI: 10.1002/ptr.2922
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Morinda citrifolia fruits on β‐amyloid (25–35) induced cognitive dysfunction in mice: An experimental and biochemical study

Abstract: The neuroprotective effect of an ethyl acetate extract of Morinda citrifolia (Rubiaceae) Linn. fruits (EMC, ethyl acetate extract of Morinda citrifolia) at doses of 200 and 400 mg/kg, p.o. was studied on beta-amyloid (25-35) peptide induced cognitive dysfunction in mice. In the step-down inhibitory avoidance, EMC exhibited a significant increase in short-term memory and long-term memory (p < 0.05). A significant decrease (p < 0.01) in escape latency was noticed in the animals in the water maze. A significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…A␤ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) is potential neurotoxic peptide for primary neuronal cortical cells which produces neurofibrillary tangles (Glenner and Wong, 1984;Masters et al, 1985) and the toxicity induced by A␤ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) in rodents resembles to AD which is suitable for the evaluation of Alzheimer's type of dementia. Previous studies suggested that accumulation of A␤ induces the reduction of habituation memory in open field exploration (Muralidharan et al, 2010) and single administration of A␤ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) in mouse through i.c.v exhibited marked amnesic effects in short term memory as well as in long term memory, in addition impaired spatial learning in water maze (Maurice et al, 1996). Water maze evaluation is an aversive method for determining cognitive function of hippocampal memory.…”
Section: Discussionmentioning
confidence: 99%
“…A␤ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) is potential neurotoxic peptide for primary neuronal cortical cells which produces neurofibrillary tangles (Glenner and Wong, 1984;Masters et al, 1985) and the toxicity induced by A␤ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) in rodents resembles to AD which is suitable for the evaluation of Alzheimer's type of dementia. Previous studies suggested that accumulation of A␤ induces the reduction of habituation memory in open field exploration (Muralidharan et al, 2010) and single administration of A␤ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) in mouse through i.c.v exhibited marked amnesic effects in short term memory as well as in long term memory, in addition impaired spatial learning in water maze (Maurice et al, 1996). Water maze evaluation is an aversive method for determining cognitive function of hippocampal memory.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Noni fruit juice has been reported to prevent neuronal damage induced by focal ischemia (Harada et al, 2009). Recently, Muralidharan et al (2010) reported that ethyl acetate extract of Noni prevented memory impairment and oxidative stress induced by amyloid beta peptide in mice.…”
Section: Introductionmentioning
confidence: 99%
“…These activities were carried out to the extent of in-vitro, in-vivo & clinical trial stages. 8 The neuroprotective effect of an ethyl acetate fruit extract of Morinda citrifolia (Rubiaceae) Linn at doses of 200 and 400 mg/kg, po was contemplated by Muralidharan et al 9 Past study by Pachauri et al was intended to examine impact of Noni on memory, cerebral blood flow(CBF), oxidative stress and AChE action in scopolamine incited amnesia mice model. 10 Harada et al inspected the impact of the juice of Morinda citrifolia (Noni juice) on the brain damage brought about by ischemic stress in mice.…”
Section: Introductionmentioning
confidence: 99%